Sequential foraging of dusky dolphins with an inspection of their prey distribution - Degrati, Mariana (2013)
The aim of this work was to analyze the sequential foraging behavior of dusky dolphins (Lagenorhynchus obscurus). Foraging sequences were defined when more than two feeding bouts occur with a traveling bout between them. We hypothesized that traveling costs of searching for prey patches were related to the time spent feeding on a patch. In addition, the distribution and seasonal variation of anchovy schools were studied in the area to better understand dolphins’ behavior. We observed dolphins from a research vessel from 2001 to 2007, and recorded their location and behavior. Anchovy data were collected during two hydro-acoustic surveys. Dusky dolphin behaviors varied seasonally; they spent a greater proportion of time traveling and feeding in the warm season (Kruskal-Wallis: H = 172.07, P < 0.01). During the cold season dolphin groups were more likely to exhibit diving behavior and less surface feeding. We found a positive correlation between searching and foraging time (r = 0.88, P = 0.019), suggesting that the costs associated with searching were compensated by an increase in the energy intake during the foraging bout. There was an association between dusky dolphin and anchovy distribution, in that they co-varied spatially and seasonally.